Social sustainability of smallholder coffee partnerships and SDG linkages in North Sumatra Province - Indah Kartika Sandra; Hendris Syah Putra; M. Fariz Afif Hasibuan (Journal of Agricultural Socio-Economics (JASE), 2026)
This study evaluates the social sustainability of a smallholder coffee partnership in Gung Pinto Village, where farmers still face production and quality constraints, limited market information, and price fluctuations. While previous research predominantly focuses on the economic outcomes of coffee supply chains, the social life cycle impact of informal smallholder partnerships remains under-investigated. The novelty of this study lies in its application of SLCIA Type I to evaluate localized social sustainability and its precise integration with regional SDG indicators in North Sumatra.  The case study was conducted in November 2025; the location was selected purposively, and 30 farmer households were selected using simple random sampling. The assessment applied the UNEP-SETAC Social Life Cycle Assessment (SLCA) framework and Social Life Cycle Impact Assessment (SLCIA) type I with performance reference points on five indicators: fair trade relations, wealth distribution, supplier relations, fulfillment of basic needs, and access to services and inputs. The results indicate that the social performance of the partnership is generally positive with an average score of 3.5, indicating compliance and, in some aspects, performance exceeding minimum standards. Access to services and inputs performed best (score 5), followed by wealth distribution (4.1), supplier relationships (3.7), and basic needs fulfillment (3.7), reflecting input and service support, increased income, improved access to basic services, and strengthened technical capacity through extension activities. Conversely, fair trade relationships scored low (1.0) due to the lack of written contracts, which can weaken the clarity of long-term rights and obligations. Overall, the partnership advances SDGs 1, 2, 6, 8, and 12 through improved income, access to basic services, and more sustainable production, while adaptive written agreements are needed to strengthen fairness and social resilience.